Saudi Arabia : Financial Sector Assessment Program Update-Detailed Assessment of Observance of the Basel Core Principles for Effective Banking Supervision. (IMF Staff Country Reports; Country Report, 2013)
This paper focuses on Saudi Arabia's Detailed Assessment of Observance of the Basel Core Principles for Effective Banking Supervision. The banking sector is fairly concentrated around a few banks. The seven largest banks have a combined share of assets of 85 percent. The three largest banks have a combined share of about 45 percent, and the next four each have market shares exceeding 5 percent. The dominant shareholders of the three largest banks are government entities, the fourth largest is linked to a family business group, and the next three have ties to major international banks. Saudi Arabia implements International Financial Reporting Standards for banks, and insurance companies, and is served by the major accounting firms.